Reduced Left Ventricular Global Longitudinal Strain in Obese Adolescents - Rilda Dwi Febrianda; Tisnasari Hafsah; Sri Endah Rahayuningsih; Dzulfikar Djalil Lukamnul Hakim; Rahmat Budi Kuswiyanto; Putria Rayani Apandi; Dida Akhmad Gurnida (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: Obesity in adolescents is associated with early cardiac structural and functional alterations that may progress to ventricular dysfunction later in life. Two-dimensional speckle-tracking echocardiography (2D STE) enables early identification of subclinical ventricular dysfunction. Nevertheless, its application in the adolescents remains limited. This study aimed to assess differences in left ventricular (LV) function among well-nourished, overweight, and obese adolescents using 2D STE.Methods: A cross-sectional study was conducted among adolescents aged 15–18 years from five senior high schools in Bandung, Indonesia between June and August 2023. Participants were randomly categorized into well-nourished, overweight, and obese groups. Transthoracic echocardiographic using M-mode and 2DSTE was performed to evaluate LV function, particularly global longitudinal strain (GLS). Statistical analyses were performed using SPSS with significance defined as p<0.05.Results: Sixty adolescents were included, 65% were male with a mean age of 16.4±0.6 years. Conventional echocardiography showed no significant differences in systolic or diastolic function among groups. However, obese adolescents demonstrated significantly greater LV posterior wall thickness and larger LV and right ventricular basal volumes compared with other groups. GLS analysis revealed significantly reduced LV deformation in obese group compared with overweight and well-nourished groups (–20.0±1.9 vs. –22.3±1.4 vs. –22.7±1.9, respectively; p<0.001).Conclusion: Reduced LV GLS detected by 2D STE indicates early subclinical myocardial dysfunction in obese adolescents despite normal conventional echocardiographic findings. Early cardiovascular screening and lifestyle interventions, including balanced nutrition and regular physical activity, may help reduce future cardiometabolic risk.